PENGARUH JARAK TANAM DAN CARA PENGENDALIAN GULMA TERHADAP PERTUMBUHAN DAN HASIL KEDELAI - Triyono, Kharis - (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2010)
ABSTRACT The experiment was conducted the study the effect of plant spacing and weed control methods on the growth and yield of soybean. The experiment was done from April to July 2009 in Jumantono Karanganyar Central Java. RCBD was used experiment with three replication. The plant spacing were 40 x 15 cm (J1) and 30 x 20 cm (J2). The four treatment of weed control methods were without weeding control (G0), twice weeding (G1), application of fomesafen herbicide (G2) and rice straw mulch (G3). The result showed that application of fomesafen herbicide decreased weed growyh and its dry weight ; and increased soybean yield. It was higher than another weed control The plant spacing effect leaves area at 6 week and soybean yield per plot. Key word : plant spacing, weed control method, soybean yield